IN VITRO STABILITY AND ANTIOXIDANT POTENTIAL OF THE NEUPROTECTIVE METABOLITE 6-HYDROXY-NICOTINE - Elena-Mihaela Mocanu; Andreea-Loredana Mazarachi; Marius Mihasan (Journal of Experimental and Molecular Biology, 2018)
Alzheimer’s disease is complex, and it is unlikely that any one single drug or intervention can successfully treat it. The implication of nicotinic acetylcholine receptors (nAChR) in Alzheimer’s disease pathogenesis has opened a new perspective on finding drugs usable for ameliorating the memory problems associated with AD. By using nAchR modulators, the availability of nAChRs for acetylcholine will be increased and the loss of forebrain cholinergic neurons associated with AD might be overcome. The microbial metabolite 6-hydroxy-D-nicotine has the ability to sustain spatial memory in rats by lowering the levels of oxidative stress in the brain and modulating the nAChRs function probably by binding to a specific site. Its success from a lab chemical to drug depends highly on its stability or shelf life. We have shown that 6-hydroxy-D-nicotine have a more potent antioxidant effect than nicotine when measured as FRAP units. Also, the pH stability of 6-hydroxy-D-nicotine is similar to nicotine, the compounds withstanding 48h exposure to pH above 3 up to 9 at room temperature.